Greening the Common Agricultural Policy: Evidence from Romania - ANDREEA - EMANUELA DRĂGOI; ANCA - CĂTĂLINA DRAGOMIR (Global Economic Observer)
Over the years, the Common Agricultural Policy (CAP) has sharpened its focus on the environment and climate with success (the so called greening process), while undergoing through a series of systemic changes that have allowed it to support a resilient and sustainable growth in the European rural areas. Analysing the impact of this greening process during 2014-2020 financial framework, our paper summarizes how CAP funding supported the sustainable and ecological development in Romania, while pointing out the main achievements and challenges. We will also highlight through a quantitative analysis based on the latest available data the implications of the greening process for Romanian agriculture using two main indicators - the evolution of Direct Payments and of environmental measures. These measures belonging to the both pillars of the CAP may underline the challenges for the Romanian farmers to obtain the necessary funding while also complying with the green standards and the no backsliding principle. Based on LEADER experience we will also show the importance of CAP funding in Romania for supporting the local communities, on several objectives: increasing employment, financing renewable energies and encouraging social inclusion in rural areas.